2018
DOI: 10.1080/09537104.2018.1457781
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA metallothionein 1 pseudogene 3 promotes p2y12 expression by sponging miR-126 to activate platelet in diabetic animal model

Abstract: Platelet hyperaggregation and hypercoagulation are associated with increase of thrombogenic risk, especially in patients with type 2 diabetes (T2D). High activity of P2Y12 receptor is found in T2D patients, exposing such patients to a prothrombotic condition. P2Y12 is a promising target for antiplatelet, but due to P2Y12 receptor constitutive activation, the clinical practical phenomena such as "clopidogrel resistance" are commonly occurring. In this study, we investigate the role of lncRNA on platelet activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…This receptor has an essential role in platelet activation (73). Zhou et al have shown that long non-coding RNA (lncRNA) metallothionein 1 pseudogene 3 (MT1P3), which is markedly upregulated in megakaryocytes of T2DM patients, enhances the expression of p2y12 receptor in platelets (74). They indicated that this is due to the inhibitory action of MT1P3 on miR-126.…”
Section: Effects Of T2dm On the Circulatory Systemmentioning
confidence: 99%
“…This receptor has an essential role in platelet activation (73). Zhou et al have shown that long non-coding RNA (lncRNA) metallothionein 1 pseudogene 3 (MT1P3), which is markedly upregulated in megakaryocytes of T2DM patients, enhances the expression of p2y12 receptor in platelets (74). They indicated that this is due to the inhibitory action of MT1P3 on miR-126.…”
Section: Effects Of T2dm On the Circulatory Systemmentioning
confidence: 99%
“…Long non-coding RNAs are a type of noncoding RNA, defined as being transcripts of more than 200 nucleotides in length, which cannot be translated into proteins (Peng et al, 2019). Excessive platelet activation is associated with an increased risk of thrombosis and there are few studies on the effects of lncRNAs on platelet activity (Zhou et al, 2019). In the current study, MEG-01 was activated with the platelet activator thrombin and it was discovered that the expression of NEAT1 was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the non-coding Metallothionein 1 Pseudogene 3 ( MT1P3 ) was found to be significantly upregulated in MKs from type 2 diabetes patients compared to healthy controls and, most importantly, had an impact on platelet activation and expression of the P2Y12 by sponging miR-126. Of note, depletion of MT1P3 by small interfering RNA (siRNA) reduced the expression of the ADP receptor, thereby inhibiting platelet activation and aggregation in a murine diabetes model [ 146 ].…”
Section: Role Of Non-coding Rnas In Megakaryopoiesis Platelet Biomentioning
confidence: 99%